A Contribution to the Flora of Kameng and Subansiri Districts, NEFA - Sahni, K. C. (Indian Forester, 1969)
The vegetation of Kameng and Subansiri Districts of NEFA is described on the basis of specimens collected which are listed ,at the end. Geography, climate and affinities of the flora are discussed. New records, rare plants, edible species, etc., are enumerated.